BUILDING A FRAMEWORK OF CUSTOMER TRUST IN AEROSTREET PRODUCT - Khoirunnisa, Fathimah; Cahyani, Fero Cahyani Arum (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2024)
This study aimed to examine the effect of information quality, perceived value, product quality, quality of service, and customer satisfaction on customer trust in Aerostreet’s products in Indonesia. The respondents data from proportionally selected Aerostreet’s customers were obtained from online questionnaires were 212 people. And then the data was analyzed using SmartPLS 3.0 to test the validity, reliability, and hypothesis of research. The results of research and examination showed that information quality and customer satisfaction had a positive and influential effect on customer’s trust, and while the perceived value, product quality, and quality of service had no effect on client’s satisfaction. This study provides empirical evidence to comprehend the effect of the psychological factor of costumer and costumer behavior towards building the customer trust towards the local brand’s product. This research can be taken demonstration by Aerostreet to initiate the marketing and product.